Electron transport in quantum dots - Bird, Jonathan P. (Boston : Kluwer Academic Publishers, 2003)
Provides coverage of topics, such as the Kondo effect and spin-dependent transport in tunnel coupled dots, quantum chaos in open quantum dots and antidot arrays, and explorations of the novel technological applications of quantum dots and carbon nanotubes. This book is useful for those involved with nanostructures and nanoelectronic devices.
1 Interactions, Spins and the Kondo Effect in Quantum-Dot Systems.- 1 Introduction.- 2 Atom-Like Properties of Electrons Confined in a Quantum Dot.- 3 Tunable Spin States with Magnetic Field.- 4 Spin Blockade in Single Electron Tunneling.- 5 Energy Relaxation with and Without Spin-Flip.- 6 The Kondo Effect in Quantum Dots.- 7 Summary.- 2 Microwave Spectroscopy on Single and Coupled Quantum Dots.- 1 Introduction.- 2 Aspects of Fabrication.- 3 Measurement Techniques.- 4 Coherent Modes in Quantum Dots.- 5 Photon Assisted Tunneling in Quantum Dots.- 6 Dynamic Response of Single Quantum Dots.- 7 The On-Chip Spectrometer.- 8 Non-Linear Transmission-Lines for Probing Single Dots.- 9 Summary.- 3 Nano-Spintronics with Lateral Quantum Dots.- 1 Introduction.- 2 Theoretical Framework.- 3 Experimental Devices and Techniques.- 4 Spin-Polarized Injection and Detection.- 5 Coulomb and Spin Blockade Spectrum.- 6 The First Few Electrons.- 7 The ? = 2 Regime.- 8 The Spin Flip Regime.- 9 Negative Differential Resistance Achieved by Spin Blockade.- 10 Conclusions.- 4 Novel Phenomena in Small Individual and Coupled Quantum Dots.- 1 Introduction.- 2 Models of Single and Double Quantum Dot Systems.- 3 Non-Gaussian Distribution of Coulomb Blockade Peak Heights in Individual Quantum Dots: Porter-Thomas Distribution of Resonance Widths.- 4 Spin and Pairing Effects in Ultra-Small Dots.- 5 Coupling between Two Dots and Leads-Coherent Many-Body Kondo States.- 6 Other Ultra-Small Devices and Phenomena.- 5 Classical and Quantum Transport in Antidot Arrays.- 1 Introduction.- 2 Antidot Arrays.- 3 Early Experiments and Pinball Model.- 4 Chaotic Dynamics in Antidot Lattices.- 5 Quantum Effects in Antidot Arrays.- 6 Random Antidot Arrays.- 7 Finite Antidot Lattices.- 8 InAs Based Arrays.- 9 Other Experiments.- 6 On the Influence of Resonant States on Ballistic Transport in Open Quantum Dots: Spectroscopy and Tunneling in the Presence of Multiple Conducting Channels.- 1 Introduction.- 2 Some Comments about Semiclassical Theories and their Underlying Assumptions.- 3 The Method of Calculation Used Primarily in this Work: A Fully Quantum Mechanical Treatment.- 4 Conductance Resonances in Open Dots.- 5 The Correspondence Between Conductance Resonances in Open Dots and Closed Dot Eigenstates.- 6 The Effect of Finite Temperature and Ensemble Averaging.- 7 Direct Comparisons of Theory with Experiment.- 8 An Alternate Semiclassical Interpretation of Transport in Open Quantum Dots: Dynamical Tunneling.- 9 Summary.- 10 Acknowledgment.- 7 A Review of Fractal Conductance Fluctuations in Ballistic Semiconductor Devices.- 1 Introduction.- 2 The Semiconductor Sinai Billiard: Can Chaos be Controlled with the "Flick of a Switch?".- 3 The Experimental Observation of Exact Self-Affinity.- 4 The Interpretation of Exact Self-Affinity.- 5 The Observation of Statistical Self-Affinity.- 6 The Classical to Quantum Transition: How do Fractals "Disappear?".- 7 The Role Played by the Billiard Walls.- 8 Conclusions.- 8 Electron Ratchets-Nonlinear Transport in Semiconductor Dot and Antidot Structures.- 1 Introduction.- 2 Non-Linear Rectification in the Quantum Regime.- 3 Nonlinear Transport in Antidot Structures.- 4 Outlook.- 9 Single-Photon Detection with Quantum Dots in the Far-Infrared/Submillimeter-Wave Range.- 1 Introduction.- 2 Fundamental Characteristics of the SET.- 3 Designing a Single-Photon Detector.- 4 Detection in Magnetic Fields.- 5 Detection in the Absence of Magnetic Field.- 6 Detector Performance.- 7 Conclusion.- 10 Quantum-Dot Cellular Automata.- 1 Introduction.- 2 The Quantum-Dot Cellular Automata Paradigm.- 3 Experimental Demonstrations of QCA: Metal-Dot Systems.- 4 Molecular QCA.- 5 Architecture for QCA.- 6 Magnetic QCA.- 11 Carbon Nanotubes for Nanoscale Spin-Electronics.- 1 Introduction.- 2 Spin Transport in Carbon Nanotubes.- 3 Conclusions.
Includes bibliographical references and index.
Keywords: Electron transport; Quantum dots